CULTURAL STUDIES ANALYSIS OF THE CONCEPT OF "TERROIR" - Victoria O. Pugacheva (Russian Studies in Culture and Society)
This article is devoted to the study of the concept of "terroir" as a socio-cultural structure. The paper presents the history of development and the main ideas of the creation of the concept of "terroir" in the context of the formation of regional cultural identity. The lack of a unified approach to determining the key characteristics of the "terroir" is due to the fact that it includes not only a set of soil and climatic features, but also cultural ones. Taking into account the difficulties of translating the term, the insufficient number of Russian-language materials, a special place in the work is occupied by a review of foreign scientific studies translated by the author on the concept of "terroir" and the identification of its role in the formation of cultural identity.